Report of a lung carcinoma extended to the left atrium through pulmonary vein - Cipriano, Federico; Dessoti, Lycio U.; Rodrigues, Alfredo José; Vicente, Walter Vilella de Andrade; Chahud, Fernando; Evora, Paulo Roberto B. (Journal of Thoracic Disease; Vol 10, No 1 (January 31, 2018): Journal of Thoracic Disease, 2017)
Lung cancers may extend along or grow through the pulmonary veins to invade or lie within the left atrium (LA). A 62-year-old man, previously healthy, presented with 1-month ventilatory-independent right hemithorax back pain, dry cough and large effort dyspnea. He also referred weight loss of 12 kg in 10 months and denied hemoptysis. As antecedents, he smoked for 40 years and moderate daily alcoholism. On physical examination, the patient was in good general condition, hydrated and regular respiration at rest [blood pressure (BP) =120/80 mmHg; heart rate (HR) =90 bpm; respiratory rate (RR) =16 rpm]. Cardiac auscultation revealed two standard rhythmic sounds without murmurs. Pulmonary auscultation revealed a slightly diminished vesicular murmur in the lower 1/3 of the right hemithorax without adventitious noises. Chest radiography showed a mass over the right lower lung. A CT scan confirmed the radiography image with the mass extending along the right inferior pulmonary vein and a tumor in the LA. Transthoracic and transesophageal echocardiography revealed large mass within the LA (occupying almost the entire cavity), measuring about 10 cm × 3 cm at its largest diameter, prolapsing into the left ventricle. Bronchoscopy, head CT scan, and whole-body bone scintigraphy investigation did not show any distant metastasis. The patient was successfully operated removing the intracardiac and inferior pulmonary vein tumor with the aid of cardiopulmonary bypass, followed by a right inferior lobectomy carried out after 25 days. After 30 days from surgery presented seizures associated a brain metastasis evidenced by CT when adjuvant radio and chemotherapy was started. During the next 90 days, the clinical conditions worsened, and the patient died 4 months after the surgical treatment. The case report has two primary justifications, even considering the poor outcome: (I) rarity and (II) the possibility of the surgical treatment.